Modeling and Experimental Studies of Obeticholic Acid Exposure and the Impact of Cirrhosis Stage. Issue 6 (15th October 2016) - Edwards, JE; LaCerte, C; Peyret, T; Gosselin, NH; Marier, JF; Hofmann, AF; Shapiro, D
Abstract : Obeticholic acid (OCA), a semisynthetic bile acid, is a selective and potent farnesoid X receptor (FXR) agonist in development for the treatment of chronic nonviral liver diseases. Physiologic pharmacokinetic models have been previously used to describe the absorption, distribution, metabolism, and excretion (ADME) of bile acids. OCA plasma levels were measured in healthy volunteers and cirrhotic subjects. A physiologic pharmacokinetic model was developed to quantitatively describe the ADME of OCA in patients with and without hepatic impairment. There was good agreement between predicted and observed increases in systemic OCA exposure in subjects with mild, moderate, and severe hepatic impairment, which were 1.4‐, 8‐, and 13‐fold relative to healthy volunteers. Predicted liver exposure for subjects with mild, moderate, and severe hepatic impairment were increased only 1.1‐, 1.5‐, and 1.7‐fold. In subjects with cirrhosis, OCA exposure in the liver, the primary site of pharmacological activity along with the intestine, is increased marginally (∼2‐fold).